PENGEMBANGAN GREEN COMMUNITY UNNES MELALUI PENGELOLAAN SAMPAH - Banowati, Eva (Indonesian Journal of Conservation, 2012)
Semarang State University (SSU) has a great possibility to conduct a natural composting as well as reaffirming SSU as the Conservation University. This research aims to: (1) find out the community perception towards waste management; (2) get the materials and information to optimalize the waste management policy for conservation environment; and (3) find an environmentally friendly location for natural composting in SSU area. The main method used in this research is survey. The population consists of SSUÃ¢â¬â¢s Civitas Academic with various status: students, officers, lecturers, and the janitors. The data gathering uses interview, documentation, observation which are analyze by using percentage description. The research result shows the community perception about waste management is still counting on the janitors only, the waste management policy for environment conservation shows the agreement among the community with the conservation vision as well as conservation behavior; the location for a good naturalcomposting is located in front of Taman Kehati, the old landfill in Banaran Village which is still being used until now, and in the Valley near the Electrical Engineering Building-ÃÂ engineering Faculty. The suggestion from this research is to merge all the composting location into one area in theÃÂ development and construction of SSU.Unnes sangat memungkinkan untuk melakukan pengomposan alami sekaligus memperkuat Unnes menjadi perguruan tinggi konservasi. Tujuan penelitian ini yakni: (1) mengetahuiÃÂ persepsi komunitas terhadap pengelolaan sampah; (2) mendapatkan bahan dan informasi untuk melakukanÃÂ kebijakan optimalisasi pengelolaan sampah untuk konservasi lingkungan; dan (3) mendapatkan lokasi pengomposan alami di area Unnes yang ramah lingkungan. Metode utama yang digunakan adalah survei. Populasinya Civitas Academica Unnes dengan status bervariasi: mahasiswa, tenagaÃÂ kependidikan, dosen, dan petugas kebersihan. Pengambilan data menggunakan wawancara, dokumentasi, observasi yang dianalisis dengan deskripsi persentase. Hasil penelitian menunjukkan persepsi komunitas terhadap pengelolaanÃÂ sampah masih mengarah pada tanggung jawab petugas kebersihan, kebijakan optimalisasi dalam pengelolaan sampah untuk konservasi lingkungan sudah menunjukkan kesepahaman anggota komunitas dengan visi konservasi dan perilaku konservasi; lokasi pengomposan alami yang baik berada di depan Taman Kehati, TPA/ S lama Desa Banaran yang kini masih dipergunakan, dan di Lembah yang berposisi di arah depan Gedung Elektro - FT. Saran yang dapat diajukan adalah lokasi pengomposan alami perlu disatukan dalam rencana pengembangan dan pembangungan Unnes.